2015
DOI: 10.1111/bjd.14019
|View full text |Cite
|
Sign up to set email alerts
|

Hand eczema and atopic dermatitis in adolescents: a prospective cohort study from the BAMSE project

Abstract: We confirm a strong association between AD during childhood and hand eczema in adolescence. Children with persistent or more severe AD are at greater risk of developing hand eczema. Asthma and/or rhinoconjunctivitis, positive specific IgE or age at onset of AD are not associated with hand eczema in adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
52
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 34 publications
6
52
0
1
Order By: Relevance
“…Although not all people with contact hand eczema have AD, people with AD are prone to hand eczema when they have 'wet' jobs that require handling irritating substances. Thus, it is of great interest to scale up occupational education and prevention measures in this group [25]. Additionally, Williams et al [27] have described cases of occupational contact dermatitis that interact with atopy to cause endogenous-like eczema, even in people who have been asymptomatic since childhood [12,15].…”
Section: Clinical Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not all people with contact hand eczema have AD, people with AD are prone to hand eczema when they have 'wet' jobs that require handling irritating substances. Thus, it is of great interest to scale up occupational education and prevention measures in this group [25]. Additionally, Williams et al [27] have described cases of occupational contact dermatitis that interact with atopy to cause endogenous-like eczema, even in people who have been asymptomatic since childhood [12,15].…”
Section: Clinical Patternsmentioning
confidence: 99%
“…Likewise, AD [25,[29][30][31]. Thus, the presence of chronic hand eczema in adults should always raise the suspicion of adult AD.…”
Section: Hand Eczemamentioning
confidence: 99%
“…In 1985, Rystedt showed that patients with persistent or recurrent AD had a significantly higher risk of having hand eczema in adulthood . This association has later been confirmed in various studies, most recently in prospective cohorts of adolescence from the general population . Other risk factors for hand eczema include female sex, contact allergy, wet work, xerosis and tobacco smoking .…”
mentioning
confidence: 91%
“…Most recent studies investigating predictors of hand eczema in the general population have focused on adolescents . Thus, research focusing on predictors of hand eczema in the adult general population is warranted.…”
mentioning
confidence: 99%
“…All children who play with homemade slime should be advised to rinse their hands thoroughly with water and apply a lipophilic or ceramide‐containing emollient after contact. We advise children with moderate to severe atopic dermatitis in our practice to avoid direct contact with homemade slime because of their risk of development of hand eczema . If needed for dermatitis, topical steroids can be prescribed, although their clinical efficacy is unclear for this condition .…”
Section: Discussionmentioning
confidence: 99%